2018
DOI: 10.1038/s41467-018-05482-0
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside-modified mRNA immunization elicits influenza virus hemagglutinin stalk-specific antibodies

Abstract: Currently available influenza virus vaccines have inadequate effectiveness and are reformulated annually due to viral antigenic drift. Thus, development of a vaccine that confers long-term protective immunity against antigenically distant influenza virus strains is urgently needed. The highly conserved influenza virus hemagglutinin (HA) stalk represents one of the potential targets of broadly protective/universal influenza virus vaccines. Here, we evaluate a potent broadly protective influenza virus vaccine ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
193
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(209 citation statements)
references
References 50 publications
2
193
0
3
Order By: Relevance
“…The highest levels of protein production and immunogenicity are observed when nucleoside-modified mRNA is also purified by high-performance liquid chromatography (HPLC) or fast protein liquid chromatography (FPLC), where aberrant double-stranded transcripts are removed. 38,46 This enhanced protective immune response has been demonstrated in mice, ferrets, and non-human primates (NHPs) against influenza 70,71 and Zika viruses, 14,15 among other targets.…”
Section: Cell-free Production and Purification Of Mrna Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest levels of protein production and immunogenicity are observed when nucleoside-modified mRNA is also purified by high-performance liquid chromatography (HPLC) or fast protein liquid chromatography (FPLC), where aberrant double-stranded transcripts are removed. 38,46 This enhanced protective immune response has been demonstrated in mice, ferrets, and non-human primates (NHPs) against influenza 70,71 and Zika viruses, 14,15 among other targets.…”
Section: Cell-free Production and Purification Of Mrna Vaccinesmentioning
confidence: 99%
“…132 Leveraging the knowledge from siRNA delivery, many laboratories have used LNP delivery of self-amplifying mRNA and conventional mRNAs against various pathogens, such as rabies, Zika, and influenza viruses, and demonstrated rapid and robust immune responses in mice, ferrets, and NHPs. [13][14][15][70][71][72] LNPs enter cells by exploiting membrane-derived endocytic pathways. Endosomal processing and release of the encapsulated genetic material into the cytosol is the rate-limiting step of delivery and a major area of research for formulation improvement.…”
Section: Self-amplifying Mrna Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most distinction between vaccine-elicited immunogenicity was observed only at the latest timepoint (20 weeks – 12 weeks after final vaccine dose), signifying variable durability of elicited antibody responses. Nucleoside-modified mRNA-LNP vaccines have been well-described to produce sustained antigen presentation with robust T follicular helper cell and germinal center B cell stimulation, resulting in extraordinarily durable antibody responses after even a single vaccine dose in small and large animals [21, 45-47]. Indeed, we identified that the durability of gB mRNA vaccine-elicited responses exceeded that of gB FL for nearly all measured antibody binding/functional responses ( Table 1 ; comparison statistically significant for: soluble and cell-associated gB binding, binding to gB domain 1 and domain 1+2, heterologous virus neutralization, and engagement of F c γRIIIa).…”
Section: Discussionmentioning
confidence: 99%
“…At present, mRNA-based vaccines have been widely studied in both infectious and noninfectious diseases, some of which are undergoing clinical trials [7][8][9][10][11][12][13]. The two main types of RNA vaccines used against influenza viruses are self-amplified mRNA (SAM) vaccine and nonreplicating mRNA vaccine.…”
Section: Introductionmentioning
confidence: 99%